2021
DOI: 10.3389/fmed.2021.657313
|View full text |Cite
|
Sign up to set email alerts
|

Protein Extraction From FFPE Kidney Tissue Samples: A Review of the Literature and Characterization of Techniques

Abstract: Most tissue biopsies from patients in hospital environments are formalin-fixed and paraffin-embedded (FFPE) for long-term storage. This fixation process produces a modification in the proteins called “crosslinks”, which improves protein stability necessary for their conservation. Currently, these samples are mainly used in clinical practice for performing immunohistochemical analysis, since these modifications do not suppose a drawback for this technique; however, crosslinks difficult the protein extraction pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…As shown in Figure a, compared to 0.5% SDS, the presence of 3% SDS in the cocktail resulted in >45% increase in the recovery of signature peptides of brentuximab and CD30, a 44% increase in the median recovery of the 40 tissue markers, as well as a 24% increase in the total protein recovery (all p < 0.05, t -test). Nonetheless, higher concentrations of SDS appeared to be counterproductive, leading to the significantly lower recovery of target signature peptides but not total protein content, which may arise from lower efficiency in delinking reaction caused by a high concentration of the anionic detergent. , Therefore, SDS concentration at 3% was determined to be optimal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure a, compared to 0.5% SDS, the presence of 3% SDS in the cocktail resulted in >45% increase in the recovery of signature peptides of brentuximab and CD30, a 44% increase in the median recovery of the 40 tissue markers, as well as a 24% increase in the total protein recovery (all p < 0.05, t -test). Nonetheless, higher concentrations of SDS appeared to be counterproductive, leading to the significantly lower recovery of target signature peptides but not total protein content, which may arise from lower efficiency in delinking reaction caused by a high concentration of the anionic detergent. , Therefore, SDS concentration at 3% was determined to be optimal.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, higher concentrations of SDS appeared to be counterproductive, leading to the significantly lower recovery of target signature peptides but not total protein content, which may arise from lower efficiency in delinking reaction caused by a high concentration of the anionic detergent. 28,29 Therefore, SDS concentration at 3% was determined to be optimal. Previously, we found that salt in SC buffer enhanced protein extraction efficiency from fresh tissues.…”
Section: Ffpe-treated Calibration Strategymentioning
confidence: 99%
“…Extraction of sufficient amount of high-quality proteins from FFPE tissue has consistently been reported to be challenging, particularly in seeding studies where the detection of misfolded αSyn was relatively low (75-76% sensitivity) [28,29]. Many studies have investigated different deparaffinization methods and extraction buffers, including commercially available FFPE protein extraction kits, to achieve a higher protein yield from FFPE tissue [46][47][48][49]. Although commercially available protein extraction kits can be effective for proteomic analysis, the extraction leaves the proteins suspended in extraction buffers that are composed of proprietary reagents, which can alter the performance of SAAs.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, proteomics technology has advanced dramatically. It is now capable of highly comprehensive and quantitative peptide profiling of archived biological materials, including Formalin-Fixed Paraffin-Embedded (FFPE) cancer tissues [ 56 , 57 ].…”
Section: Proteomics In Osteosarcomamentioning
confidence: 99%